1993
DOI: 10.1063/1.352756
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the properties of a-SiGe:H films: Roles of deposition rate and hydrogen dilution

Abstract: Device quality a-SiGe:H thin films have been deposited by radio-frequency plasma-assisted. decomposition of silane and germane diluted with and without hydrogen. Improvement in structural atid electronic'prop@ies have been achieved employing low deposition rate and high hydrogen dilution. It has been observed that low deposition rate can reduce the preferential attachment of H to silicon throughout the alloy region while the beneficial effect of hydrogen dilution is more effective in a low band gap region (E,<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…One possible reason may relate to the sticky nature of GeH 3 species more than the SiH 3 species. The diffusion length of GeH 3 species is less than SiH 3 species during the growth of SiGe alloy [24], which makes it more difficult to reach the energetically favorable sites on the film surface. As a result, Ge is easier to form weak bonds than Si in SiGe binary network.…”
Section: Ge-incorporation In Amorphous and Crystalline Silicon-germanmentioning
confidence: 99%
“…One possible reason may relate to the sticky nature of GeH 3 species more than the SiH 3 species. The diffusion length of GeH 3 species is less than SiH 3 species during the growth of SiGe alloy [24], which makes it more difficult to reach the energetically favorable sites on the film surface. As a result, Ge is easier to form weak bonds than Si in SiGe binary network.…”
Section: Ge-incorporation In Amorphous and Crystalline Silicon-germanmentioning
confidence: 99%
“…Therefore, the preparation of high quality a-SiGe:H thin film becomes an important research issue. Over the past years, several studies have been made on improvement in the properties of a-SiGe:H films, such as Middya et al which showed that improvement in structural and electronic properties have been achieved by employing low deposition rate and high hydrogen dilution in a diode PECVD [7]. Xu et al showed that the hydrogen plasma annealing method eliminates the a-SiGe:H defect states to improve films quality by conventional RF-PECVD [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed [ 17,18] that helium dilution effects are due to the enhanced bombardment of the film surface by helium ions during growth. This also can explain the seemingly lesser Ge incorporation at lower pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Several seemingly partly contradictory optimum growth conditions have been suggested which include, among others: a) reducing short lifetime radicals through reaction with H2 or avoiding depletion of germane [ 10]; b) enhancing surface diffusion of Ge related radicals by hydrogen coverage [ 11]; c) using an alternative Ge dangling bond terminator [12]; d) needing no [13], versus high energy ion bombardment (or high ion bombardment at high deposition rate [14]) to reduce heterogeneities and obtain optimum performance [9,[15][16] e) using higher electron temperatures for the PECVD process to obtain a favourable discharge chemistry [ 16]; f) needing low [17,18] versus high [19,20,21] deposition rates.…”
Section: Introductionmentioning
confidence: 99%